Adverse events and stroke prevention by interventional left atrial appendage occlusion in patients with low CHA2DS2‐VASc score—results from the multicenter German LAARGE registry. Issue 7 (6th April 2022) - Fastner, Christian; Brachmann, Johannes; Lewalter, Thorsten; Zeymer, Uwe; Sievert, Horst; Ledwoch, Jakob; Geist, Volker; Hochadel, Matthias; Schneider, Steffen; Senges, Jochen; Akin, Ibrahim; Ansari, Uzair
Abstract: Background: Interventional left atrial appendage occlusion (LAAO) is routinely performed in patients with nonvalvular atrial fibrillation and contraindications to standard anticoagulation. Aims: We investigated its role in patients at low stroke risk, and compared the effectiveness and safety in patients with low versus high risk. Methods: LAARGE is a prospective registry depicting the clinical reality of LAAO. LAAO was conducted with different standard commercial devices, and follow‐up period was 1 year. Patients with started procedure and documented CHA2 DS2 ‐VASc score were selected from the whole database. Results: A total of 638 patients from 38 centers were divided into CHA2 DS2 ‐VASc score ≤2, i.e., low‐risk group (10.2%), and >2, i.e., high‐risk group (89.8%). The latter had a pronounced cardiovascular risk profile and preceding strokes (0% vs. 23.9%; p < 0.001). Implantation success was consistently high (97.6%), frequencies of intrahospital major adverse cardiac and cerebrovascular events (0% vs. 0.5%) and other major complications (4.6% vs. 4.0%) were low (each p = not significant [NS]). Numerous moderate complications were also observed in the low‐risk patients (12.3% vs. 9.4%; p = NS). Frequencies of nonfatal strokes (0% vs. 0.7%) and severe bleedings (0% vs. 0.7%) were low (each p = NS). In a specific analysis, patients at very high risk of stroke (i.e., CHA2 DS2 ‐VASc score >4) did not have increased rates of complications or nonfatal strokes in the first year after the procedure. Conclusions: Low‐risk patients had no nonfatal strokes and major bleedings within 1 year after hospital discharge but had unexpectedly high rates of moderate procedural complications. The indication in these patients should be strictly defined based on an individual benefit‐risk assessment.